Decision Support System for Determination of Decoration Service Employee Using Weighted Product Method (Case Study on Sanggar Puri Ethnic Decoration). Issue 1 (February 2021) - Gunawan, H; Maramdhani,; Chazar, C; WArthana, Y
Abstract: The amount of expertise needed to complete a decoration services project makes the leaders of the Puri Ethnic Decoration studio often have difficulty in making decisions to determine employees in accordance with the criteria of the project to be worked on. The method used in making the decision to determine the decoration service employee uses the Weighted Product (WP) method in the form of a Weighted Product (WP) calculation based on the amount of quota available in each project. The results of this study are in the form of a decision support system application that employee alternative solutions will be involved in the decoration service project.